Distance and Connection. Phonograph Records as Narrative Objects in 1940s Cinema - Straw, Will (Revue musicale OICRM, 2023)
This article examines a corpus of American musicals of the 1940s to observe the use made within them of phonograph records. My hypothesis is that, across these films, the phonograph record becomes a key token in the structuring of relationships within narratives. Records function as objects connecting people and places; they become mediators of interpersonal connection and carriers of cultural expression. The article is concerned, in particular, with the gender relations that form around phonograph records, during a period when radio disc jockeys, jukebox operators, and other agents in the world of music were often represented by women characters.